Autotrophic and heterotrophic contributions to short-term soil CO 2 efflux following simulated summer precipitation pulses in a Mediterranean dehesa - Casals, Pere; Lopez-Sangil, Luis; Carrara, Arnaud; Gimeno, Cristina; Nogués, Salvador (Global Biogeochemical Cycles, 2011)
Autotrophic and heterotrophic components of soil CO2 efflux may have differential responses to environmental factors, so estimating the relative contribution of each component during summer precipitation pulses is essential to predict C balance in soils experiencing regular drought conditions. As even small summer rains induced high instantaneous soil respiration rates in Mediterranean wooded grasslands, we hypothesized that standing dead mass, surface litter, and topsoil layer could play a dominant role in the initial flush of CO2 produced immediately after soil rewetting; in contrast, soil CO2 effluxes during drought periods should be mostly derived from tree root activity. In a grazed dehesa, we simulated four summer rain events and measured soil CO2 efflux discontinuously, estimating its d 13 C through a Keeling plot nonsteady state static chamber approach. In addition, we estimated litter contribution to soil CO2 efflux and extracted soil available C fractions (K2SO4‐extracted C and chloroform‐fumigated extracted C). The d 13 C‐CO2 from in‐tube incubated excised tree roots and rewetted root‐free soil was −25.0‰ (±0.2) and −28.4‰ (±0.2), respectively. Assuming those values as end‐members’ sources, the autotrophic component of soil CO2 efflux was dominant during the severe drought, whereas the heterotrophic contribution dominated from the very beginning of precipitation pulses. As standing dead mass and fresh litter contribution was low (<25%) in the first day and negligible after, we concluded that CO2 efflux after rewetting was mostly derived from microbial mineralization of available soil organic C fractions.
Keywords: d13C; Drought; precipitation manipulation (voyant); Soil CO2 efflux

Soil CO2 efflux and extractable organic carbon fractions under simulated precipitation events in a Mediterranean Dehesa - Casals, Pere; Gimeno, Cristina; Carrara, Arnaud; Lopez-Sangil, Luis; Sanz, MJosé (Soil Biology and Biochemistry, 2009)
The magnitude of CO2 efﬂux pulses after rewetting a dry soil is highly variable and the factors regulating these pulses are poorly understood. In this ﬁeld experiment, we aimed to study the C dynamics after simulated summer rainstorms in a Mediterranean open holm oak woodland (dehesa). We hypothesized that because the herbaceous cover is mostly dead during the summer in this ecosystem, the short-term CO2 efﬂux (SR) after rewetting could mainly be explained by different measurable soil C fractions: i) K2SO4-extracted soil C (EOC); ii) microbial biomass C (MBC); or iii) chloroform-fumigated extracted C (CFE). On both grazed and abandoned dehesa sites, we simulated three summer rain events at two-week intervals and we measured SR discontinuously in three plots under tree canopy and in another three plots in open grassland. In each plot, C fractions and water content were estimated before (2 h) and after (36 h) each irrigation event. Following rewettings, SR increased up to ten times compared with nonirrigated plots. The CFE actually increased after rewetting in the ﬁrst two irrigations but not in the third event, suggesting that the capacity of the soil to release labile organic C from soil aggregates or litter was reduced after each irrigation event. Overall, the C released as CO2 in the ﬁrst 24 h was related to the CFE existing before rewetting, which may help to explain the spatial variability in SR. However, the explained variability decreased after each irrigation, suggesting a change to a less labile composition of the CFE fraction as a consequence of multiple drying-rewetting cycles
Keywords: Chloroform-fumigation K2SO4-extraction; drying-rewetting cycles; holm oak savanna woodland; Soil C fractions; Soil respiration

Soil CO2 efflux and extractable organic carbon fractions under simulated precipitation events in a Mediterranean Dehesa - Casals, Pere; Gimeno, Cristina; Carrara, Arnaud; Lopez-Sangil, Luis; Sanz, MJosé (Soil Biology and Biochemistry, 2009)
The magnitude of CO2 efﬂux pulses after rewetting a dry soil is highly variable and the factors regulating these pulses are poorly understood. In this ﬁeld experiment, we aimed to study the C dynamics after simulated summer rainstorms in a Mediterranean open holm oak woodland (dehesa). We hypothesized that because the herbaceous cover is mostly dead during the summer in this ecosystem, the short-term CO2 efﬂux (SR) after rewetting could mainly be explained by different measurable soil C fractions: i) K2SO4-extracted soil C (EOC); ii) microbial biomass C (MBC); or iii) chloroform-fumigated extracted C (CFE). On both grazed and abandoned dehesa sites, we simulated three summer rain events at two-week intervals and we measured SR discontinuously in three plots under tree canopy and in another three plots in open grassland. In each plot, C fractions and water content were estimated before (2 h) and after (36 h) each irrigation event. Following rewettings, SR increased up to ten times compared with nonirrigated plots. The CFE actually increased after rewetting in the ﬁrst two irrigations but not in the third event, suggesting that the capacity of the soil to release labile organic C from soil aggregates or litter was reduced after each irrigation event. Overall, the C released as CO2 in the ﬁrst 24 h was related to the CFE existing before rewetting, which may help to explain the spatial variability in SR. However, the explained variability decreased after each irrigation, suggesting a change to a less labile composition of the CFE fraction as a consequence of multiple drying-rewetting cycles
Keywords: Chloroform-fumigation K2SO4-extraction; drying-rewetting cycles; holm oak savanna woodland; Soil C fractions; Soil respiration